Effects of a structured educational intervention on metabolic control of type-1 diabetes mellitus patients - Bernie Endyarni; Jose RL Batubara; I Boediman (Indonesian Pediatric Society, 2006)
Background Children with type-1 diabetes face not only short-term complications but also long-term microvascular andmacrovascular complications. Therefore, a continuing medical careand education to reach blood glucose near normal range is abso-lutely required. An addition of behavioral educational interventionto intensive diabetes management resulted in improved metaboliccontrol and quality of life.Objective To determine the effects of a structured educationalintervention to parents and patients with type-1 diabetes mellituson their knowledge and patient metabolic control.Methods In this interventional study with pretest-posttest designat Department of Child Health, Medical School, University of Indo-nesia, a total of 21 patients with the age between 8 and 18 yearsand their parents were assigned to follow a structured educationalprogram over period of 6 months. During the 6 intervention ses-sions, some procedures were applied: obtaining HbA1c at initial,3 rd and 6 th month using HPLC procedure, classroom teaching pro-gram, small group discussions, role-playing and pre-posttests.Results The mean HbA1c level in the 21 children and adoles-cents at initial, 3 rd and 6 th month were 10.05% (SD 2.67%), 10.28%(SD 2.23%) and 10.01% (SD 2.67%), which showed no significantchanges (P>0.05). After 6 educational sessions, the result showedsignificant changes in both parents’ (P<0.05) and patients’ knowl-edge (P<0.05). Patients’ diabetes-related knowledge had a mod-erate correlation (r=-0.632; P=0.02) , but parents’ diabetes-relatedknowledge had no significant correlation (r=-0.348; P=0.122) withpatient mean HbA1c level.Conclusion A structured educational intervention used in this studyis able to improve parents’ and patients’ diabetes-related knowl-edge significantly. Patients’ diabetes-related knowledge had a sig-nificant correlation with metabolic control